2020
DOI: 10.4103/aian.aian_560_20
|View full text |Cite
|
Sign up to set email alerts
|

Neurological symptoms as initial manifestation of Covid-19 – An observational study

Abstract: Background: Respiratory system involvement and fever are considered as a cardinal manifestation of Covid-19 infection for the screening of case detection. We (India) are into the fourth month of Covid-19 and cases are still rising, this could mean that fever and respiratory symptoms may not be the only initial symptoms. Therefore, we intend to investigate whether neurological symptoms can precede the cardinal symptoms. Methods: Totally, 391 Covid-19 RTPCR positive hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Of note, among the four studies with the longest follow-up time (i.e. 57.94 ±1.40 58 , 62 (range 25–95) 73 , 117 (range 41–193) 99 and 125 (45- 215) 100 days after symptom onset) recovery rates were 54%, 89%, 88% and 84%, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Of note, among the four studies with the longest follow-up time (i.e. 57.94 ±1.40 58 , 62 (range 25–95) 73 , 117 (range 41–193) 99 and 125 (45- 215) 100 days after symptom onset) recovery rates were 54%, 89%, 88% and 84%, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Studies carried out in India by JaseelaMajeed et al, on 206 deceased patients showed that 50.5% of the deceased had preexisting co morbidities, with Diabetes and Hypertension being the most commonly seen 6 . Another study carried out in central India by Dosi R et al, on 365 patients admitted in a tertiary care center described 47.1% of the population as having co-morbidities and Hypertension was the most commonly seen7 . A metaanalysis done by Wern Hann NG et al, on 150 articles from April to September 2020 revealed Chronic Kidney Disease, Diabetes Mellitus, Hypertension to be individually linked to mortality from COVID19.…”
mentioning
confidence: 98%